2009
DOI: 10.1103/physrevc.79.044316
|View full text |Cite
|
Sign up to set email alerts
|

High-spin level structure inMo94,95

Abstract: High-spin level structures of 94,95

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Chemical reactivity between them, controlled by the covalency of their Cu -O -Cu bonds, stabilises the overall crystal structure kinetically by zero point fluctuations of the Cu-O bond-length, oscillating between 1.93 and 1.83Å. This is evidenced experimentally in the double peak structured PDF (pair-distribution function) [30] and in the splitting of the Cu -O -Cu bond stretch mode [31]. The fluctuations of the bond-length go hand in hand with double charge fluctuations on such deformable plaquettes favouring textured meso-structures, as seen in STM-IS (scanning tunnelling microscope imaging spectroscopy) [32][33][34] [35].…”
Section: Resonating Bipolaronsmentioning
confidence: 96%
“…Chemical reactivity between them, controlled by the covalency of their Cu -O -Cu bonds, stabilises the overall crystal structure kinetically by zero point fluctuations of the Cu-O bond-length, oscillating between 1.93 and 1.83Å. This is evidenced experimentally in the double peak structured PDF (pair-distribution function) [30] and in the splitting of the Cu -O -Cu bond stretch mode [31]. The fluctuations of the bond-length go hand in hand with double charge fluctuations on such deformable plaquettes favouring textured meso-structures, as seen in STM-IS (scanning tunnelling microscope imaging spectroscopy) [32][33][34] [35].…”
Section: Resonating Bipolaronsmentioning
confidence: 96%
“…Thermodynamic properties are used to characterize constraint-satisfaction problems such as the N -queens and Latin problems [15,16]. In these studies, the possibility of phase-transition at system size N → ∞ is investigated, however, no phase transition is found.…”
Section: Anomaly In Thermodynamic Propertiesmentioning
confidence: 99%
“…The investigation of the thermodynamic properties will give us information not only on the most optimized network, but also on the second, third, or subsequent "most optimized" configurations. In addition, thermal properties are used to characterize constraintsatisfaction problems such as N -queens and Latin problems [15,16]. Therefore, we investigate the thermodynamic properties of these ensembles in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…For 92 Zr, Werner et al, reported the pure neutron configuration to the 2 + 1 state, while the second excited quadrupole state shows the signatures of the one-phonon mixed-symmetric 2 + state [40]. The results of an in-beam study of high-spin structure of 94,95 Mo at GASP, Legnaro was reported in [41]. In this work the authors also reported shell model results in π(p 1/2 , g 9/2 , d 5/2 ) and ν(p 1/2 , g 9/2 , g 7/2 , d 5/2 , d 3/2 , s 1/2 ) space.…”
Section: Introductionmentioning
confidence: 96%